DETECTION OF ESBL, AMPC AND METALLO BETA- LACTAMASE MEDIATED RESISTANCE IN GRAM- NEGATIVE BACTERIA ISOLATED FROM WOMEN WITH GENITAL TRACT INFECTION - Shilan S. Ahmad; Fattma A. Ali (European Scientific Journal, ESJ, 2014)
This study was carried out during the period (March to July 2012). A total of two hundred and fifty high vaginal swabs were collected from (100 pregnant and 150 non- pregnant) women patients with genital tract infection at the age ranged between (18- 55) years, who attended the gynecology clinics and obstetrics department of Maternity Teaching Hospital in Erbil city. Vaginal swab samples were collected and direct examined for microscopic Gram stain examination and culture techniques. Isolated microorganisms were identified using microscopical, morphological, biochemical tests, analytic profile index system and also identification and sensitivity test were performed by Vitek 2 compact system. The results showed that positive vaginal cultures of Gram- negative bacteria isolates obtained from women patients were 73 isolates, which distributed among pregnant 20 (27.4%) and non- pregnant women 53 (72.6%) is not significant according to statistical analysis. All Gram negative bacterial (73) isolates were screened for their ability to produce extended spectrum β- lactamases enzymes by using double disk diffusion method. Out of 45 (61.6%) were found to be extended spectrum β- lactamases producers, which distributed among pregnant 9 (45%) and non- pregnant 36 (67.9%) but statistical analysis not significant. All Gram negative bacteria were screened for their ability to produce Ampicillin resistant gene (AmpC) β- lactamase enzyme by using Disk antagonism test. Out of (73) Gram negative bacteria isolates, 5 (6.8%) were found to be AmpC β- lactamase producers. All Gram negative bacteria were screened for their ability to produce metallo β- lactamase enzyme by using Imipenem- EDTA (Ethylene diamine tetra acetic acid) combined disc test. Out of (73) Gram negative bacteria isolates, 25 (34.2%) were found to be metallo β- lactamase producers, which distributed among pregnant 5 (25%) and non- pregnant 20 (37.7%). Among all Gram negative bacterial isolates were screened for their ability to produce (Extended spectrum β- lactamases, AmpC and metallo β- lactamase) enzymes and the results revealed that most of isolates produce more than one type of β- lactamase enzymes, for example all Escherichia coli isolates 30 (71.4%) were extended spectrum β- lactamases producers and 19 (45.2%) were metallo β- lactamase producers.